Magnesium Sulphate For Tetanus, review of two cases - Susanto, Tirta Darmawan (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction: Tetanus is critically ill disease with long term hospitalization period. It need to be carefully monitored, usually in intensive care unit and involves critical care physicians. Benzodiazepine is preferred by World Health Organization (WHO) for muscle spasm control in tetanus, but it will be less costly if magnesium sulphate can be used alone to control spasm and autonomic dysfunction in tetanus. We report a series of 2 tetanus cases that were treated using magnesium sulphate to provide a brief clinical description about the use of magnesium sulphate in tetanus. We also give a brief review on epidemiology, pathophysiology, clinical findings, diagnosis, and treatment of tetanus to provide implications for intensive care physicians. Methods : Case series reportResults : Two patients with tetanus was given magnesium sulphate infusion to control muscle spasm and autonomic dysfunction with good results as expected. Both of them were survive and discharged home in healthy condition.Conclusions :Magnesium sulphate can also be used to control muscle spasm and autonomic dysfunction although WHO recommend benzodiazepines for controlling muscle spasm. Intensive care physicians should have enough knowledge about tetanus and how it should be managed adequately to ensure survival from tetanus.